2013
DOI: 10.2147/copd.s48967
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy of aclidinium versus glycopyrronium and tiotropium, as maintenance treatment of moderate to severe COPD patients: a systematic review and network meta-analysis

Abstract: BackgroundAclidinium bromide is a new long-acting muscarinic antagonist (LAMA) indicated for maintenance bronchodilator treatment of chronic obstructive pulmonary disease (COPD). The efficacy of aclidinium was compared with tiotropium and glycopyrronium, using a network meta-analysis (NMA) of randomized controlled trials (RCTs) in moderate-to-severe COPD patients.MethodsA systematic review was performed to identify RCTs evaluating aclidinium 400 μg twice daily (BID), glycopyrronium 50 μg once daily (OD), tiotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 36 publications
3
31
0
Order By: Relevance
“…(1) Karabis and colleagues conducted a network meta-analysis which demonstrated that AB produced similar improvements in lung function, health-related quality of life, and dyspnea compared with TIO-SMI, TIO-DPI, and GPM [Karabis et al 2013]. (2) Pharmacotherapies in COPD have never been shown to improve TIO-DPI, tiotropium-dry powder inhaler; TIO-SMI, tiotropium-soft mist inhaler.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) Karabis and colleagues conducted a network meta-analysis which demonstrated that AB produced similar improvements in lung function, health-related quality of life, and dyspnea compared with TIO-SMI, TIO-DPI, and GPM [Karabis et al 2013]. (2) Pharmacotherapies in COPD have never been shown to improve TIO-DPI, tiotropium-dry powder inhaler; TIO-SMI, tiotropium-soft mist inhaler.…”
Section: Discussionmentioning
confidence: 99%
“…Karabis and colleagues conducted a network meta-analysis comparing AB, TIO-SMI, TIO-DPI and GPM and concluded that AB was as effective as other LAMAs in improving lung function, health-related qualify of life and symptoms [Karabis et al 2013]. However, COPDrelated exacerbations were not included in their analysis.…”
Section: Introductionmentioning
confidence: 99%
“…This estimation was based on the assumption that CFB for post-bronchodilator FEV 1 was equal to CFB for FEV 1 trough (ie, the use of a short-acting β 2 -agonist for the postbronchodilator measurement would not affect the CFB FEV 1 values). The CFB values for FEV 1 trough for each arm were estimated with a network meta-analysis (NMA) 17. Finally, the FEV 1 % predicted was calculated at 12 and 24 weeks as the ratio of post-bronchodilator FEV 1 /predicted FEV 1 .…”
Section: Methodsmentioning
confidence: 99%
“…The results of an NMA for the CFB trough FEV 1 endpoints at 12 and 24 weeks were used in the economic model to estimate the decline of the FEV 1 % predicted during the first 24 weeks of the time horizon as a result of the efficacy of treatments (short-term changes in trough FEV 1 ). NMA results of the comparison between aclidinium 400 μg bid and tiotropium 18 μg od were taken from a larger NMA that also compared aclidinium 400 μg bid and tiotropium 5 μg od;17 however, since tiotropium 5 μg od is not a relevant comparator in the United States, a scenario analysis was performed comparing only aclidinium 400 μg bid and tiotropium 18 μg od, and these latter results were used to populate the present model. NMA results were used, as no long-term studies have been conducted comparing aclidinium and tiotropium 20.…”
Section: Methodsmentioning
confidence: 99%
“…Maintenance treatment with aclidinium should be expected to provide similar results to tiotropium in patients with moderate-to-severe COPD. 43 As noted above, the vast majority of published clinical trials to date compare aclidinium bromide with placebo to assess its effect on FEV 1 and COPD symptoms. Although published data are limited, current ongoing clinical trials are directly comparing aclidinium, alone or in combination with formoterol, to formoterol or salmeterol/fluticasone.…”
Section: Comparative Clinical Trialsmentioning
confidence: 99%